2003
DOI: 10.1248/bpb.26.1225
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Soluble 1,3/1,6-.BETA.-D-Glucan, SCG in Sera of Naive DBA/2 Mice

Abstract: A branched beta-glucan from Sparassis crispa (SCG) is a major 6-branched 1,3-beta-D-glucan showing antitumor activity. In the present study, we examined the anti-SCG antibody in naive mice by ELISA. Using SCG coated plate, sera of naive DBA/1 and DBA/2 mice contained significantly higher titers of antibody than other strains of mice. Anti-SCG Ab titers of each DBA/1 and DBA/2 mice were significantly varied. Using various polysaccharide-coated plate, sera of DBA/2 mice also reacted with a beta-glucan from Candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 15 publications
0
30
1
1
Order By: Relevance
“…4). Although detection of an anti-β-glucan antibody in normal human and mouse sera has been reported previously (17,27), we found, for the first time, the presence of anti-Sophy β-glucan IgG antibody in serum samples prepared from the umbilical cord blood of neonates. The mechanism(s) of production of anti-Sophy β-glucan IgG antibody in the blood of adult donors and neonates remains poorly understood at the present time; however, our data strongly suggest that innate as well as acquired immunity is established by anti-β-glucan antibody in living organisms for host defenses even from the time of birth.…”
Section: Immunological Actions Of Sophy β-Glucancontrasting
confidence: 54%
“…4). Although detection of an anti-β-glucan antibody in normal human and mouse sera has been reported previously (17,27), we found, for the first time, the presence of anti-Sophy β-glucan IgG antibody in serum samples prepared from the umbilical cord blood of neonates. The mechanism(s) of production of anti-Sophy β-glucan IgG antibody in the blood of adult donors and neonates remains poorly understood at the present time; however, our data strongly suggest that innate as well as acquired immunity is established by anti-β-glucan antibody in living organisms for host defenses even from the time of birth.…”
Section: Immunological Actions Of Sophy β-Glucancontrasting
confidence: 54%
“…13,14) Furthermore, although -glucans have long been considered to exhibit weak antigenicity, we reported that not only innate immune responses but also acquired immune responses, such as the production of antibodies against -glucans, are involved in the immunostimulatory effects of -glucans. 15,16) Very recently, we found that a unique type of -D-glucan obtained from the polymorphic fungus Aureobasidium pullulans (this -Dglucan is termed as AP-FBG) reacted to the antibodies in human sera; this -D-glucan has a mixed structure comprising a 1,3--D-glucan backbone with single 1,6--D-glucopyranosyl-branching units at every 2 nd residue as the major structure and a 1,3--D-glucan backbone with single 1,6--D-glucopyranosyl-branching units at every 3 rd residue as the minor structure (the ratio of the major and minor units was approximately 7:3). 17) The reactivity of AP-FBG was stronger than that of -Dglucan obtained from Grifola frondosa (GRN), which comprises a 1,3--D-glucan backbone with single 1,6--D-glucopyranosyl-branching units at every 3 rd residue, 18,19) while it was weaker than that of -glucan from Candida albicans (CSBG), which comprises a 1,3--Dglucan backbone with long 1,6--D-glucopyranosylbranching units.…”
Section: Involvement Of Branched Units At Position 6 In the Reactivitmentioning
confidence: 99%
“…It has been recorded that β-glucan content of S. crispa is about 43.6% as measured by enzyme method by Japan Food research laboratories. Thus, S. crispa can be utilized for mass production of β-glucan [8]. Kimura [3] reported that the medicinal value of this mushroom is mainly due to 6-branched 1‚3-beta-glucan (SCG).…”
Section: Introductionmentioning
confidence: 99%